Pengaruh Beasiswa Pemkab Jember Terhadap Meningkatnya IPK Belajar Mahasiswa MPI UIN KHAS JEMBER - Hurmawani, Dewi; Sahdiyah, Holilatus; Abrori, M Firdan; Amalia, Novi Nur; Hidayat, Rofiq (JMPI: Jurnal Manajemen, Pendidikan dan Pemikiran Islam, 2024)
This research aims to investigate the influence of the Jember District Government Scholarship on the Improvement of the Cumulative Grade Point Average (CGPA) of students in the Islamic Education Management program at the State Islamic University Kiai Haji Achmad Siddiq Jember. The scholarship serves as an additional support program for students to complete their higher education programs, based on their main considerations of achievements and specific excellence they possess. The existence of this scholarship program can alleviate the financial burden on financially disadvantaged students. Moreover, these scholarships can also enhance the quality of education in Indonesia. The main focus of this research is on the specific influence of the Jember District Government Scholarship on students in the Islamic Education Management program at the State Islamic University Kiai Haji Achmad Siddiq Jember. This study employs a quantitative approach with a causal-comparative method using online questionnaire data collection, followed by regression analysis to determine the relationship between scholarship variables and GPA improvement. The findings indicate a significant positive influence between receiving the Jember District Government Scholarship and the improvement of the Cumulative Grade Point Average (CGPA). Therefore, it can be concluded that the provision of the Jember District Government Scholarship can contribute positively to the Cumulative Grade Point Average (CGPA), thus having significant implications for educational policies and student financial assistance.